Pathogenetic substantiation of thiotriazoline use on the basis of disorders of proteolysis processes and protease inhibitors under conditions of contact dermatitis and experimental pneumonia - Regeda-Furdychko, M. M. (Journal of Education, Health and Sport, 2019)
The aim of our research was to to investigate the features of the proteinase-inhibitory system in guinea pig lungs in the dynamics of the formation of experimental contact dermatitis (ECD) and experimental pneumonia (EP) and to establish the correction of their disorders by thiotriazoline. Materials and methods. The researches were carried out on 60 guinea-pigs which were divided into 6 groups. I group (control) were intact guinea-pigs, II group – were animals with an ECD and EP (4th day), III group – were guinea-pigs on the 8th day of the experiment, IV group consisted of animals with an experimental CD and EP (10th day) and V group included guinea-pigs with an combined pathology (18th day, without thiotriazoline using). The last sixth group included animals with an ECD and EP that were treated by thiotriazoline from the 8th to the 18th days of the experiment. Two periods of development of ECD and EP were distinguished: early (4th and 8th days of experiment) and late (10th and 18th days). Experimental contact dermatitis was simulated by method of VA Volkovoj (2010). EP was called by the method of VN Shlyapnikov, TL Solodov (1998). Thiotriazoline was administered intramuscularly at a dose of 100 mg per 1 kg of weight daily from the 8th to the 18th days of the experiment. The condition of proteinase-inhibitory system was determined by lysis of the azoalbumin, azokasein and azokolagen and maintenance content of α1-protease inhibitor (α1-PI), α2-macroglobulin (α2-М) by method of Veremeenko K.N., Goloborodko O.P. (1988). Results and discussion. It is established that under the conditions of development of experimental contact dermatitis and experimental pneumonia there are changes in the proteinase-inhibitory system, which is manifested by activation of proteolysis. There was an increase in the level of azoalbumin, azocasein and azocollagen, especially on the 18th day of the experiment and depression of protease inhibitors. This led to the formation of proteinase-inhibitory imbalance before treatment. The use of thiotriazoline led to the correction of proteolysis (their reduction) and the growth of protease inhibitors in the lungs with the development of contact dermatitis and experimental pneumonia, which indicated its corrective effect on impaired proteinase-inhibitory system markers and its appropriate pathogenetic justification.